2020
DOI: 10.1002/jpen.1772
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Nurses’ Involvement in Artificial Nutrition and Hydration at the End of Life: A Scoping Review

Abstract: This review aimed to summarize existing nursing literature to provide an overview of the extent, range, and nature of nurses’ involvement in artificial nutrition and hydration (ANH) at the end of life and to map the key concepts underpinning nurses’ involvement in ANH. A scoping review was designed following the methodological framework guidelines of Arksey and O'Malley and the recommendations for advancing the methodology by Levac et al. An inductive qualitative content analysis was conducted according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 74 publications
(161 reference statements)
0
13
0
Order By: Relevance
“…Studies have indicated that those who were older had a higher level of education and had longer years of work experience had better knowledge resources as well as better skills in utilizing the resources. Nursing staff who worked at the oncology or hospice unit had more experience in care [18,19,21] and also diligently cultivated clinical talents [13]. In particular, clinical nursing staff who had participated in hospice care training had a more positive attitude towards non-ANH in terminal patients when the patient's body system deteriorates [15,21,22], and a significantly positive correlation was observed when clinical nursing staff had a better understanding of the concept of hospice care and the timing and decision-making for ANH, they had a more positive attitude towards accepting ANH [5,14,15,21,22].…”
Section: IVmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have indicated that those who were older had a higher level of education and had longer years of work experience had better knowledge resources as well as better skills in utilizing the resources. Nursing staff who worked at the oncology or hospice unit had more experience in care [18,19,21] and also diligently cultivated clinical talents [13]. In particular, clinical nursing staff who had participated in hospice care training had a more positive attitude towards non-ANH in terminal patients when the patient's body system deteriorates [15,21,22], and a significantly positive correlation was observed when clinical nursing staff had a better understanding of the concept of hospice care and the timing and decision-making for ANH, they had a more positive attitude towards accepting ANH [5,14,15,21,22].…”
Section: IVmentioning
confidence: 99%
“…Hence it is evident that clinical nursing staff lack relevant competencies in palliative care. In clinical practice, the members of a hospice care team are capable of independent thinking and judgment and may discuss the pros and cons of ANH as well as ethical dilemma encountered in clinical practice with physicians, so as to reduce the psychological burden and confusions of family members [1,3,4,6,10,13,14,22], which will affect the conveyance of the knowledge relating to the administration of ANH in terminal patients when the patient's body system deteriorates and help to bring out professional care competence. Therefore, insufficient recognition and unfamiliar attitude of nursing staff on hospice care along with insufficient knowledge of relevant practices in hospice care will affect the quality of hospice care provided to the terminal patients [4,5,13].…”
Section: IVmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, it is widely accepted that nursing staff may play a key role in PC in order to promote a consensus between appropriate treatment choices and the patients' preferences that may finally facilitate the decision of applying this process [11,12]. Accordingly, the lack of knowledge and skills in PC from nurses may lead to erroneous perceptions related to approaching these patients [13]. Previous studies have reported that this lack of knowledge or skills referring to end-of-life care started during the academic stage [14].…”
Section: Introductionmentioning
confidence: 99%
“…Provision of nutrition and hydration enterally or intravenously, commonly referred to as artificial nutrition and hydration may be considered but, with a few exceptions, is not generally considered best practice near the end of life as numerous studies have identified little benefit and even negative outcomes, from aggressive efforts to maintain “normal” nutrition and hydration in those nearing death (Druml et al., 2016; Good, Richard, Syrmis, Jenkins‐Marsh, & Stephens, 2014a, 2014b; Raijmakers et al., 2011; Teno et al., 2012). The role nurses play in artificial nutrition and hydration decision‐making near end of life varies by setting and country (Albanesi et al., 2020).…”
Section: Introductionmentioning
confidence: 99%